Associations of body fat percentage with C-reactive protein levels in Canadian adults with and without osteoarthritis: Findings from the Canadian Longitudinal Study on Aging (CLSA) - Kendal A. Marriott; Paul W. Stratford; Chris P. Verschoor; Dawn M. E. Bowdish; Marina Mourtzakis; Jaclyn N. Chopp-Hurley; Emily G. Wiebenga; Monica R. Maly (PLoS ONE, 2026)
Objectives Determine the cross-sectional associations of serum inflammation with body composition and physical capacity in Canadian adults with/without osteoarthritis (OA) and multimorbidities. Methods 30,097 participants from the Canadian Longitudinal Study on Aging were categorized into eight subgroups (presence/absence of lower extremity OA, hand OA, multimorbidities), disaggregated by sex. Linear regression models (multiple covariates and log-transformed CRP) were completed with body composition and physical function measures as dependent variables. A priori, the research team defined that an increase in the adjusted R 2 between models by 1% or more was considered a meaningful change in explanatory power. Results Higher CRP levels [standardized β(95%CI)] was associated with greater whole body fat percent [females 0.14 (0.13, 0.16), males 0.13 (0.12, 0.15)], trunk fat percent [females 0.16 (0.15, 0.18), males 0.13 (0.12, 0.15)] and lower appendicular lean mass index [males −0.12 (−0.13, −0.11)], independent of OA or multimorbidity. Conclusions There were small but meaningful associations between CRP and each of percent adiposity and appendicular lean mass index. These associations were present regardless of OA and multimorbidity status. Percent adiposity, but not OA status, was consistently associated with systemic inflammation, suggesting that adiposity driven inflammation may contribute to OA related health outcomes.